Pengaruh Efikasi Diri dan Motivasi terhadap Keberhasilan Usha pada Pemilik Toko Pakaian di Pusat Grosir Metro Tanah Abang, Jakarta - Mei Ie; Eni Visantia (Universitas Kristen Maranatha, 2013)
A lot of factor affecting business success, among others are self-efficacy and motivation. This study was conducted to determine the influence of self-efficacy and motivation to business success. The population was all of shop owner in PusatGrosir Metro Tanah Abang, Jakarta. The purposive sampling methods used in this research. The methods of data collection were conducted by distributing questionnaires to 50 respondents. The techniques of data analysis were using multiple regression analysis. The findings of this research showed that self-efficacy and motivation simultaneously affect to business success. While the self-efficacy is partially affect to business success and motivation also is partially affect to business success.